KETERSEDIAAN NUTRIEN DAN GROSS ENERGY HIJAUAN SORGUM VARIETAS SAMURAI II DENGAN SISTEM RATUN PADA USIA POTONG DAN DOSIS PUPUK UREA YANG BERBEDA - Harahap, Anwar Efendi (Unpad Press, 2024)
Sorghum is a forage plant that has the ability to produce new shoots or saplings known as ratoons. This research aims to evaluate the nutritional dynamics and GE (gross energy) of Samurai II sorghum variety due to differences in treatment at harvest age and urea fertilizer dosage. This study used a completely randomized factorial design (3 x 3) with 3 replications. The first factor is the harvest age of 80, 85, and 90 days, and the second factor is the urea fertilizer dose of 200, 300, and 400 kg ha-1. The parameters observed were crude protein, crude fat, crude fiber, ADF, NDF and GE levels. The results of the research showed that the Samurai II variety of sorghum had a significant effect on dry matter due to the treatment of cutting age in the primary harvest and ratoon 1. Furthermore, there was a difference (P<0.05) due to the sorghum dose. application of urea fertilizer to crude fiber in the primary and ratoon 2 harvests. In the Samurai II variety of sorghum there was also an interaction between cutting age and the dose of urea fertilizer in the primary and ratoon 2 harvests on the NDF content produced. The nutritional value and GM content are still stable even when cut up to ratoon 2 (third harvest)